1997
DOI: 10.1046/j.1365-2141.1997.562704.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and modulation of cellular receptors for interferon‐γ, tumour necrosis factor, and Fas on human bone marrow CD34+ cells

Abstract: Summary.Interferon-g (IFN-g), tumour necrosis factor-a (TNF-a) and Fas-ligand can mediate potent inhibitory signals in haemopoietic cells. Clinical and laboratory studies have suggested the involvement of these cytokines in the regulation of normal haemopoiesis and in the pathophysiology of bone marrow (BM) failure syndromes. As the effects of cytokines may also be regulated at the cellular receptor level, we studied the expression and modulation of TNF receptor (TNFR), IFN-gR and Fas-R on haemopoietic progeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
1
5

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 39 publications
2
59
1
5
Order By: Relevance
“…11 Raza et al 4,21 also observed an increase of TNF-␣, TGF-␤ and IL-1␤ in the bone marrow of MDS. Sato et al 31 have reported that IFN-␥,TNF-␣ and FasL can mediate potent inhibitory signals in hematopoietic cells. Fas antigen expression on CD34-positive bone marrow cells was increased by TNF-␣ and IFN-␥ in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…11 Raza et al 4,21 also observed an increase of TNF-␣, TGF-␤ and IL-1␤ in the bone marrow of MDS. Sato et al 31 have reported that IFN-␥,TNF-␣ and FasL can mediate potent inhibitory signals in hematopoietic cells. Fas antigen expression on CD34-positive bone marrow cells was increased by TNF-␣ and IFN-␥ in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it has been shown that TGF-␤ or TNF-␣ both influence the CD95/ CD95L system by modulating CD95R expression in blood cells. 49,50 The influence of both cytokines on CD95L has not been described so far.…”
Section: Discussionmentioning
confidence: 99%
“…It included both a modulation of death signaling through the death receptor CD95 as well as an increase of Bcl-2 related proteins promoting apoptosis. Cooperation at the level of CD95 involved as one element the IFNg mediated increase of cell surface expression of CD95, which has previously also been seen in other cell types (Friesen et al, 1996;Sato et al, 1997;Ossina et al, 1997). The other element was the MycN mediated increase of cellular susceptibility towards the death signal that is initiated from CD95.…”
Section: Participants In Mycn/ifng Apoptosis Of Neuroblastoma Cellsmentioning
confidence: 99%